Bromide and chloride distribution across the snow‐sea ice‐ocean interface: A comparative study between an Arctic coastal marine site and an experimental sea ice mesocosm. Issue 8 (6th August 2016) - Xu, Wen; Tenuta, Mario; Wang, Feiyue
Abstract: During springtime in the Arctic, bromine explosion events occur when high concentrations of reactive bromine species are observed in the boundary layer with the concurrence of ozone depletion events and mercury depletion events. While a variety of substrates including snow, sea ice, frost flowers, and aerosols have been proposed to be the substrate and/or source of bromine activation in the Arctic, recent studies have highlighted the role of snow. Here we report concentration profiles of halides (Br − and Cl − ), Na +, and mercury across the snow‐sea ice‐seawater interface at a coastal marine site in the Canadian Arctic Archipelago in March and June 2014, as well as in an experimental sea ice mesocosm in Winnipeg in January and February 2014. The occurrence of bromine activation at the Arctic site in March was indicated by the high mercury concentrations in snowpack. At both the Arctic and mesocosm sites, the molar ratios of Br − /Na + were nearly constant throughout the sea ice depth, but highly variable in the upper layer of the overlying snowpack, revealing that bromine activation takes place in the sunlit snow instead of sea ice. This is supported by calculations showing that the loss of Br – from the upper layer of the snowpack is large enough to produce the observed concentrations of reactive bromine in the atmospheric boundary layer. However, the upper layer of the Arctic snowpack tends to be generally enriched in Br – due to the net addition of Br – ‐containing gases and nonsea‐salt aerosols. Key Points: Arctic springtime bromine activation occurs in the upper, sunlit layer of snowpack Arctic springtime bromine activation does not occur on or in sea ice Upper layer of Arctic snowpack is generally enriched in bromide due to the net addition of bromide‐containing gases and nonsea‐salt aerosols